Penetration Testing Berbasis OWASP Testing Guide Versi 4.2 (Studi Kasus: X Website) - Dharmawangsa, I Dewa Gede Govindha; Sasmita, Gusti Made Arya; Pratama, I Putu Agus Eka (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 4 No 1 (2023): JITTER, Vol.4, No.1, April 2023DO - 10.24843/JTRTI.2023.v04.i01.p06, 2023)
Government website is one of the strategies in e-government development, x  agency follows this strategy by having a website with address x, along with these developments, cyber attacks through websites also increase, therefore it is necessary to carry out periodic testing and evaluation of websites with penetration testing. Penetration testing is the security testing for network or website to find vulnerabilities that could be exploited by attackers. This research is supported by the OWASP Testing Guide Framework Version 4.2 with 12 modules covering all aspects of security testing on websites. The results of the penetration testing is found vulnerabilities then be assessed for with CVSS Calculator 3.1 and given recommendations afterward. This research finds 32 vulnerabilities, 12 of that vulnerabilities have an impact on the website with 4 vulnerabilities that have a medium risk, 5 vulnerabilities that have a high risk and 2 vulnerabilities that have a critical risk.